Pengaruh Akuntabilitas Dan Transparansi Terhadap Kinerja Pemerintah Daerah Dimediasi Oleh Pengawasan Keuangan Pada Pemerintah Daerah Provinsi Papua - Orpaniati Rantepulung; Julius Ari Mollet; Westim Ratang (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2023)
The Effect of Accountability and Transparency on Local Government Performance Mediated by Financial Supervision in the Papua Provincial Government, supervised by Westim Ratang and J. A. Mollet. Thesis for Masters in Regional Finance at Cenderawasih University.The purpose of this research is to know and analyze the effect; 1) Financial accountability for the performance of the regional government of the Papua Province, 2) Financial transparency towards the performance of the regional government of the Papua Province, 3) Financial accountability for the regional financial supervision of the Papua Province, 4) Financial transparency for the regional financial supervision of the Papua Province, 5) Financial accountability, transparency finance and financial supervision affect the performance of the regional government of Papua Province, 6) Financial accountability to the performance of local government through financial supervision of the regional government of Papua Province, 7) Financial transparency of the performance of local government through financial supervision of the regional government of Papua Province and 8) Financial supervision on the performance of the regional government of the Papua Province, 9) Variables that have a dominant influence on the performance of the regional government of the Papua Province.The method used in this research is path analysis. The author uses path analysis (path analysis) because to determine causal relationships, with the aim of explaining the direct or indirect influence between exogenous variables and endogenous variables.The results of the analysis show that: (1) Financial accountability influences regional financial management supervision. (2) Financial transparency affects regional financial management supervision. (3) Financial accountability influences local government performance. (4) Financial transparency affects local government performance. (5) Financial accountability, financial transparency and financial supervision affect the performance of local governments. (6) Financial accountability affects the performance of regional governments through supervision of regional financial management. (7) Financial transparency influences regional government performance through supervision of regional financial management. (8) Supervision of regional financial management affects the performance of regional governments. (9) Accountability has a dominant influence on the performance of the regional government of Papua Province.Â